Otoprotective Effects of α-lipoic Acid on A/J Mice With Age-related Hearing Loss. Issue 6 (July 2020) - Huang, Shanshan; Xu, Ang; Sun, Xiumei; Shang, Wenjing; Zhou, Bingxin; Xie, Yi; Zhao, Mengmeng; Li, Ping; Lu, Peng; Liu, Tingyan; Han, Fengchan
Abstract : Objective: A/J mice are a mouse model of age-related hearing loss (AHL) with progressive degeneration of outer hair cells (OHCs), spiral ganglion neurons (SGNs), and stria vascularis. This study was carried out to observe the otoprotective effects of α-lipoic acid on A/J mice. Methods: A/J mouse pups at postnatal day 7 were randomly distributed into the untreated group, the dimethyl sulfoxide (DMSO) group, and the α-lipoic acid + DMSO group. α-lipoic acid was given to the mice intraperitoneally at a dosage of 50 μg/g body weight every other day. Time course auditory-evoked brainstem response (ABR) thresholds were tested. OHC loss was counted and the densities of SGNs and the width of stria vascularis were measured at 4 and 8 weeks of age. Results: Measurement of the ABR thresholds revealed that hearing loss in A/J mice was attenuated by α-lipoic acid at age from 3 to 8 weeks. Moreover, preservation effects of OHCs, SGNs, and stria vascularis by α-lipoic acid were observed in the cochleae of A/J mice at 4 and 8 weeks of age. Conclusion: Hearing loss in A/J mice can be attenuated by α-lipoic acid. The otoprotective effects of α-lipoic acid on A/J mice may be obtained by preserving OHCs, SGNs, and stria vascularis in the cochleae. The oxidative damage related to gene mutations may be a potential target for AHL prevention and therapy. Abstract : Supplemental Digital Content is available in the text